Self-rated health, psychosocial functioning, and health-related behavior among Thai adolescents - Randy M. Page (2018)
Background: Despite the popularity of self-rated health (SRH) in Western countries as a useful public health tool, it has only rarely been used in Asian countries. The purpose of the current study was to determine whether measures of psychosocial functioning and health-related factors differ according to SRH in a school-based sample of Thai adolescents. Methods: The survey was given to 2519 adolescents attending 10 coeducational secondary high schools in Chiang Mai Province, Thailand and included measures of psychosocial functioning (loneliness, hopelessness, shyness, perceptions of social status, self-rated happiness, and perception of physical attractiveness) and certain health-related factors (height/weight, physical activity, eating breakfast, sleep). Results: The proportion of boys (5.1%) reporting that they were not healthy was similar to the proportion of girls (4.6%) making the same rating. These adolescents showed a pattern of overall poor health risk. Compared to adolescent peers who rated their health as healthy or very healthy, they were less physically active, got less sleep, were more likely to be overweight, and scored lower on loneliness, shyness, hopelessness, and self-rated happiness. Conclusions: The present pattern of poor health risk warrants attention and supports the merit of using SRH in adolescent health assessment. SRH is easy to obtain and simple to assess and single-item assessments of SRH appear to be valid measures of health status in adults and adolescent. Interventions, such as health counseling, mental health counseling, and health education, can target adolescents who rate themselves as 'not healthy' or report poor health status. © 2008 Japan Pediatric Society.